1992
DOI: 10.1002/hon.2900100605
|View full text |Cite
|
Sign up to set email alerts
|

Production of multiple cytokines by Hodgkin's disease derived cell lines

Abstract: The production of cytokines was analysed in Hodgkin's disease (HD) derived cell lines by enzyme linked immunosorbent tests (ELISA) and Northern blot experiments. Our results demonstrate that HD derived cell lines produce a variety of cytokines, such as IL1 alpha, IL4, IL5, IL6, IL8, TNF alpha, TNF beta and GM-CSF but not IL1 beta, IL2, IL3 and G-CSF. In cell lines with a high expression of CD25 (the light chain of the IL2 receptor), we found soluble IL2 receptors in the supernatants. In addition, receptors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…4,37 The results of immunofluorescence staining for gp80 are in line with our previous reports showing the expression on all analyzed cell lines with the exception of KMH2. 3,4 The recently established HD cell line L1236 also expressed gp80, but at a low level ( Figure 4B). The results of Western blot and flow cytometry analyses are summarized in Table 1, which also provides IL-6 levels detected by ELISA.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…4,37 The results of immunofluorescence staining for gp80 are in line with our previous reports showing the expression on all analyzed cell lines with the exception of KMH2. 3,4 The recently established HD cell line L1236 also expressed gp80, but at a low level ( Figure 4B). The results of Western blot and flow cytometry analyses are summarized in Table 1, which also provides IL-6 levels detected by ELISA.…”
supporting
confidence: 91%
“…We and other groups have previously shown that IL-6 and IL-6R gp80 are expressed both in HD cell lines and in primary H-RS cells and IL-6, and perhaps additional cytokines may be involved in the pathogenesis of HD. 1,[3][4][5][6] The aim of this study was to evaluate whether IL-6 signal transduction is important for the growth of HD cell lines. Using a panel of well-characterized HD cell lines we identified constitutively activated DNA-binding proteins in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations